2015
DOI: 10.1016/j.ntt.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and behavioral effects of intranasal administration of silver nanoparticles

Abstract: Use of silver nanoparticles (AgNPs) for their antimicrobial properties is widespread. Much of the previous work on the toxicity of AgNPs has been conducted in vitro or following oral or intravenous administration in vivo. Intranasal (IN) instillation of AgNPs mimics inhalation exposure and allows further exploration of the toxicity of these particles via respiratory tract exposure. The present study involved 1) single-dose exposures to assess tissue distribution and toxicity and 2) repeated exposures to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 35 publications
2
37
1
Order By: Relevance
“…In the present study, we observed the presence of silver containing particles in lungs and in tissues beyond the air-blood barrier, both in the 1h/d and 4h/d exposure group. Not surprisingly, nanoparticles were identified in liver and spleen of both 1h/d and 4h/d exposure groups by TEM associated to EDX and sp ICP-MS analysis, as previously reported by others (Davenport et al 2015, Gosens et al 2016, Lebedovà et al 2016. Importantly, our analysis also allowed identifying for the first time silver containing nanoparticles in the placenta after maternal inhalation exposure.…”
Section: Accepted Manuscript Discussionsupporting
confidence: 84%
“…In the present study, we observed the presence of silver containing particles in lungs and in tissues beyond the air-blood barrier, both in the 1h/d and 4h/d exposure group. Not surprisingly, nanoparticles were identified in liver and spleen of both 1h/d and 4h/d exposure groups by TEM associated to EDX and sp ICP-MS analysis, as previously reported by others (Davenport et al 2015, Gosens et al 2016, Lebedovà et al 2016. Importantly, our analysis also allowed identifying for the first time silver containing nanoparticles in the placenta after maternal inhalation exposure.…”
Section: Accepted Manuscript Discussionsupporting
confidence: 84%
“…Ag NPs up-regulated heme oxygenase-1 (HO-1) expression at both the gene and protein levels in the hippocampus, but not in the cortex, after mice were exposed through intranasal instillation [ 73 ]. Another study using microarray analyses [ 74 ] found that, after mice were treated with Ag particles (25 nm), the expression of 18 genes in the caudate nucleus, 14 in the frontal cortex, and 29 in the hippocampal area were altered.…”
Section: Reviewmentioning
confidence: 99%
“…A study involving mice exposed to AgNPs by intranasal instillation showed, upregulated heme oxygenase‐1 expression at both gene and protein levels in the hippocampus and not in the cortex (Davenport et al, ). A related study with rat brain also revealed gene expression in the cortex and hippocampus were altered due to OS caused by AgNPs (Huang, Hsiao, Lin, Wang, & Huang, ; Rahman et al, ).…”
Section: Silver Nanoparticles: Blood–brain Barrier and Neurotoxicitymentioning
confidence: 99%